Improving Elementary School Students' Understanding of Citizens' Rights and Obligations Through Active Civics Learning - Anastasiya, Dinda (International Journal of Students Education, 2025)
This study aims to improve elementary school students' understanding of the rights and obligations of citizens through the implementation of active Citizenship Education (PKN) learning. The research method that I used is the "literature review" method for the title "Improving Elementary School Students' Understanding of Citizens' Rights and Obligations Through Active PKN Learning" this study uses the 'literature review' method which aims to explore students' understanding of the rights and obligations of citizens through citizenship education (PKN) learning by focusing on the collection, evaluation and critical analysis of scientific works that are relevant to a particular research topic. This study shows that a learning approach that involves active student participation can improve their understanding of the concept of rights and obligations as citizens. As a result, students not only understand the theory, but are also able to apply citizenship values in everyday life. Active PKN learning has proven to be effective in encourage students to be more critical, and responsible as part of society and various societies and countries the main goal of civic education is to foster insight and awareness of the state, attitudes and behaviors that love the homeland and are based on the nation's culture, the archipelago's insight, and national resilience in the future successors of the nation who are studying and will master science and technology and art. In addition, it also aims to improve the quality of Indonesian people who are noble, have personality, are independent, advanced, tough, professional, responsible, and productive as well as physically and mentally healthy.